Migration and social mobility in Burkina Faso: Historical perspectives on the migration divide - Anne Sofie Westh Olsen (Danish Institute for International Studies (DIIS), 2014)
Mobility is a resource and a privilege that is unevenly distributed between countries, and within countries. People from developing countries depend on visas and residence permits to a larger extent than citizens of the developed world. Most migration policy research determines the inequality of mobility mainly as a consequence of restrictive immigration policies in destination countries. The focus of this paper is instead on the limited access order that has led to unequal access to migration between people from an African sending country, which has been largely overlooked. This paper shows the historical emergence of a migration divide between intercontinental and intra-African migrants. Through a historical analysis, the paper underlines how academic migration to France became a means to social mobility in Burkina Faso after independence, while today there is a breakdown of the social elevator via migration since preferential access to migration is likely to enhance the divide between rich and poor.
Keywords: 300; migration divide; academic migration; return migration; elite formation; Upper Volta/Burkina Faso